Identification and antigenicity of the Babesia ovis spherical body protein 4 (SBP4) - Uluçeşme M. C.; Keskin S.; Özübek S.; Doymaz M. Z.; Aktaş M. (My University, 2024)
Babesia ovis is the primary causative agent of acute and chronic babesiosis in small ruminants. The disease poses serious challenges to the sheep industry, leading to significant economic losses, particularly in tropical and subtropical regions worldwide. Advanced diagnostic methods and identification of vaccine candidate antigens are crucial for effective ovine babesiosis control. The SBP4 protein, initially identified in B. bovis, is conserved among various geographical isolates and has demonstrated excellent performance as a serological antigen in several ELISA formats for detecting bovine babesiosis. Using the B. bovis SBP4 as a query, BLAST searches were conducted on an uncurated B. ovis genome assembly, followed by PCR amplification and sequencing of a newly identified Bo-SBP4. Characterization of this novel gene and protein was carried out using bioinformatics analysis, and ELISA. The serological response to the Bo-SBP4 protein during acute infection and post-infection periods was determined in lambs experimentally infected with the B. ovis-Alacakaya strain. Five lambs were experimentally infected, and blood and serum samples were collected daily for the first 30 days postinfection and biweekly for one year after the acute phase. The presence of specific antibodies against rBoSbp4 was tested in serum samples, and antibodies in some experimental animals remained positive for 400 days post-infection. The Bo-SBP4 protein shows potential as a candidate for developing a novel serological test to detect B. ovis infection in sheep.
Keywords: Yaşam Bilimleri; Mikrobiyoloji; İmmünoloji; Viroloji; Temel Bilimler; Life Sciences; Microbiology; Immunology; Virology; Natural Sciences; Temel Bilimler (Sci); Yaşam Bilimleri (Life); Doğa Bilimleri Genel; Çok Disiplinli Bilimler; Natural Sciences (Sci); Life Sciences (Life); Natural Sciences General; Multidisciplinary Sciences; Mikrobiyoloji (tıbbi); İmmünoloji ve Mikrobiyoloji (çeşitli); Multidisipliner; Sağlık Bilimleri; Microbiology (medical); Immunology and Microbiology (miscellaneous); Multidisciplinary; Health Sciences